In situ filler addition for homogeneous dispersion of carbon nanotubes in multi jet fusion-printed elastomer composites - Chen, Jiayao (2023)
The dispersibility of fillers determines their effect on the mechanical properties and anisotropy of the 3D-printed polymeric composites. Nanoscale fillers have the tendency to aggregate, resulting in the deterioration of part performance. An in situ filler addition method using the newly developed dual-functional toughness agents (TAs) is proposed in this work for the homogeneous dispersion of carbon nanotubes (CNTs) in elastomer composites printed via multi jet fusion. The CNTs added in the TAs serve as an infrared absorbing colorant for selective powder fusion, as well as the strengthening and toughening fillers. The printability of the TA is theoretically deduced based on the measured physical properties, which are subsequently verified experimentally. The printing parameters and agent formulation are optimized to maximize the mechanical performance of the printed parts. The printed elastomer parts show significant improvement in strength and toughness for all printing orientations and alleviation of the mechanical anisotropy originating from the layer-wise fabrication manner. This in situ filler addition method using tailorable TAs is applicable for fabricating parts with site-specific mechanical properties and is promising in assisting the scalable manufacturing of 3D-printed elastomers.